Vacuum Energy in Saez-Ballester Theory and Stabilization of Extra Dimensions - Pheiroijam Suranjoy Singh; Kangujam Priyokumar Singh (Universe, 2022)
In this work, we study a spherically symmetric metric in 5D within the framework of Saez-Ballester Theory, where minimal dark energy-matter interaction occurs. We predict that the expanding isotropic universe will be progressively DE dominated. We estimate few values of the deceleration parameter, very close to the recently predicted values. We obtain the value of the DE EoS parameter as <semantics>ω=−1</semantics>. Additionally, we measure the value of the overall density parameter as <semantics>Ω=0.97(≈</semantics>1), in line with the notion of a close to or nearly (not exactly) flat universe. We predict that the model universe starts with the Big-Bang and ends at the Big Freeze singularity. In general, we cannot find conditions for stabilization of extra dimensions in general relativity, and all dimensions want to be dynamical. Here, we present two possible conditions to solve this stabilization problem in general relativity.